Variation of the Intermediate Language in Flanders - N. A. Kolomiets (Дискурс)
Introduction. At this time the  language  continuum  of Dutch on the  territory of Flanders undergoes  significant changes  and develops in the direction of three-part  paradigm, which consists  of the  standard  Dutch language,  intermediate (tussentaal)  and  various  dialects which explains the actuality of the studies of the intermediate language. The purpose of the study is to analyze the variety of the intermediate language, its components, combinations and correlation  between  the dialect features  and the features  of the standard language, as well as to analyze the problem of distinguishing the dialects and the intermediate language which explains the novelty of the study.Methodology and  sources. The study of conducted  using the  publications  and articles  in Dutch (Flanders), TV series,  talk-show on the Flemish TV, interviewing some  informants.  The data was collected  and analyzed using the method  linguistic observations, questioning  and comparative analysis. The theoretical  basis of the research is language variation.Results  and  discussion.  In  the  intermediate  language  of  the  language  continuum  of Flanders  there  are  different  variants  which are  formed  due  to  the  interference of  the primary, secondary  and tertiary dialect features, as well as due to the interference of the elements of the standard  language in different degrees.  There are general  features  of the intermediate language typical for all territory of Flanders on the one side and on the other side  local  differences. The  intermediate  language  gains  strong  positions  in the  media, culture and advertising.Conclusion.  Some dialect features  have a high degree  of interference in all variants of the intermediate  language  in  Flanders,  they  become  an  integral  part  of  the  intermediate language  and  don’t  prevent  the  speakers   from  understanding   each  other.  Due  to  the dominant  regional character of the variants of the intermediate language native speakers can easily identify the origin of the respondent.